ANALISIS PENDAPATAN DAN PENGELUARAN RUMAH TANGGA PETANI PADI DESA SUKAJAWA, KECAMATAN BUMIRATU NUBAN, KABUPATEN LAMPUNG TENGAH - Sugesti, Mei Tri; Abidin, Zainal; Kalsum, Umi (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2015)
The purpose of this research were to find out the total income of rice farmers’ household, the expenditure of farmers’ household, and the factors that influence the expenditure of rice farmers’ household. The research was conducted in Sukajawa village, Bumiratu Nuban subdistrict, Central Lampung regency. The number of respondent was 47 rice farmers. This study found that the total income of rice farmers in Sukajawa was Rp29,243,662.00 per year, 87.54% of on farm, 0.91% of off farm and 11.55% of non farm. The expenditure of rice farmers’ household in that village was Rp20,545,157.00 per year, 80.94% was allocated for primary needs such as food and 19.06% for other needs. It could be concluded that the income of Sukajawa rice farmers was relatively low, because most of their income was used for food. The factors that influenced rice farmers’ expenditures were income level (X1), family member (X2),and the area of the rice field (X5). Key words: expenditure, farmers, household, income